IEEE GLOBECOM 2007 - IEEE Global Telecommunications Conference 2007
DOI: 10.1109/glocom.2007.839
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Energy-Efficient Cooperative Routing in Wireless Networks

Abstract: Abstract-Recently, cooperative routing in wireless networks has gained much interest due to its ability to exploit the broadcast nature of the wireless medium in designing powerefficient routing algorithms. Most of the existing cooperationbased routing algorithms are implemented by finding a shortestpath route first. As such, these routing algorithms do not fully exploit the merits of cooperative communications at the physical layer. In this paper, we propose a cooperation-based routing algorithm, namely, Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 14 publications
0
79
0
Order By: Relevance
“…Function of MAC layer mainly reliable t ransmission, access mechanism control, and also security [7,8,9]. Procedure of data transmission and reception, data addressing, data fragmentation, packets formatting is depends on MAC sub-layer.…”
Section: About the Wlan Cooperati Ve Mac Schemementioning
confidence: 99%
“…Function of MAC layer mainly reliable t ransmission, access mechanism control, and also security [7,8,9]. Procedure of data transmission and reception, data addressing, data fragmentation, packets formatting is depends on MAC sub-layer.…”
Section: About the Wlan Cooperati Ve Mac Schemementioning
confidence: 99%
“…In [3], the cooperative routing problem is studied for static wireless networks, where the multi-hop diversity technique is used to combine signals at the destination. The minimum power cooperative routing algorithm is proposed in [4], which makes full use of the cooperative communications while constructing the minimumpower route.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cooperative routing problem has been considered in [2], [3], [4]. In [2], the minimum energy cooperative path routing algorithm was introduced, where a cooperative shortest path algorithm was developed for cooperative routing in stationary wireless networks.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], the authors demonstrated that the minimum energy cooperative path (MECP) routing problem is NP-complete, and then proposed a cooperative shortest path routing algorithm to achieve nearly the MECP. In [9], the authors proposed the Minimum Power Cooperative Routing (MPCR) algorithm, which constructs the minimum-power route with certain throughput guaranteed. In [10], the authors proposed the CoopGeo protocol, which provides an efficient approach to select the next hop as well as the optimal relay based on cross-layer designed geographic routing.…”
Section: Introductionmentioning
confidence: 99%